Improving nil by mouth patient care - Rajbardhan Singh Rajpoot; Abdurrahman Nagjar; Ibrahem Dokali; Humna bilal Lodhi; Izlam Taq (Clinical Medicine, 2025)
Background: Patients placed on ‘nil by mouth’ (NBM) orders are not consistently assessed for adequate fluid and nutrient intake, leading to potential risks of dehydration and malnourishment. Additionally, many patients do not receive sufficient maintenance fluids and nutrients while on NBM.This quality improvement project aimed to improve the daily assessment of NBM patients for hydration and nutritional status, ensuring timely interventions, such as intravenous (IV) fluids, dietician and Speech and Language Therapy (SALT) referrals, and the resumption of oral intake. Method: This quality improvement project was conducted as a retrospective audit, focusing on the review of 20 patient records accessed through HIVE (an Electronic Patient Record system). This project benefited from collaboration with the SALT team, whose contributions were instrumental in identifying key gaps and shaping the interventions.Data collection focused on 11 key questions to evaluate NBM care practices, including whether the reason for NBM was documented; the start and stop times were recorded; referrals to the SALT team and dieticians were made within 24 h; IV fluids were initiated for patients NBM for more than 6–12 h; and daily assessments of hydration, malnourishment and NBM status were documented. Documentation of sufficient fluid intake and resumption of oral intake (including NG tube) within 24 h were also assessed. Results: Baseline data (n=20): 95% of patients had their reason for NBM documented; 70% of patients had their NBM start date and time documented; 77.8% of patients had their NBM stop date and time documented; 90% of patients were referred to the SALT team within 24 h; 50% of patients who were NBM for more than 6–12 h received IV fluids; 80% of patients were referred to a dietician within 24 h; 55% of patients resumed oral intake within 24 h; 5% of patients had a daily assessment of dehydration documented; 10% of patients had a daily assessment of malnourishment status documented; 47.4% of patients had a daily review of NBM status documented; 65% of patients were documented as taking sufficient fluids. Recommendations: Conduct teaching sessions to emphasise the importance of accurate and timely NBM documentation and daily review;Develop and implement a standardised NBM documentation template to ensure all required fields (reason, start/stop times and daily reviews) are completed;Ensure adequate maintenance fluids and nutrients;Conduct follow-up audits to monitor compliance and identify further gaps. Conclusion: This project identified key gaps in NBM patient care and proposed actionable solutions to improve daily assessments and interventions. A follow-up audit will be conducted after implementing these recommendations to evaluate progress and ensure continuous improvement.